Association of lumbosacral transitional vertebra and sacroiliitis in patients with inflammatory back pain suggesting axial spondyloarthritis. (31st October 2019) - Carvajal Alegria, Guillermo; Voirin-Hertz, Marie; Garrigues, Florent; Herbette, Marion; Deloire, Lucile; Simon, Alexandre; Feydy, Antoine; Reijnierse, Monique; van der Heijde, Désirée; Marhadour, Thierry; Saraux, Alain
Abstract: Objective: Lumbosacral transitional vertebras (LSTVs) are common in the general population, but their potential impact on the sacroiliac joints is unclear. We aimed to determine the prevalence of LSTVs and to assess their associations with sacroiliitis by standard radiography and MRI in a population with suspected axial spondyloarthritis. Methods: The data were from the DESIR cohort of 688 patients aged 18–50 years with inflammatory low back pain for ⩾3 months but <3 years suggesting axial spondyloarthritis. The baseline pelvic radiographs were read by two blinded readers for the presence and type (Castellvi classification) of LSTVs. Associations between LSTVs and other variables collected at baseline and at the diagnosis were assessed using the χ 2 test (or Fisher's exact test) or the Mann–Whitney test. Results: LSTV was found in 200/688 (29.1%) patients. Castellvi type was Ia in 54 (7.8%), Ib in 76 (11.0%), IIa in 20 (2.9%), IIb in 12 (1.7%), IIIa in 7 (1.0%), IIIb in 21 (3.0%) and IV in 10 (1.4%) patients. Compared with the group without LSTVs, the group with LSTVs had higher proportions of patients meeting modified New York criteria for radiographic sacroiliitis (19% vs 27%, respectively; P = 0.013) and Assessment of SpondyloArthritis international Society MRI criteria for sacroiliitis (29% vs 39%, respectively; P = 0.019). Conclusion: In patients with inflammatory back pain suggesting axial spondyloarthritis, LSTVs are associated with both radiographic and MRI sacroiliitis.